Prognostic impact of inappropriate defibrillator shocks in a population cohort. Issue 17 (6th March 2013) - Deyell, Marc William; Qi, Anzhen; Chakrabarti, Santabhanu; Yeung-Lai-Wah, John Ah-Fan; Tung, Stanley; Khoo, Clarence; Bennett, Mathew T; Qian, Hong; Kerr, Charles R
Abstract : Background: There is a relative paucity of data linking inappropriate implantable cardioverter-defibrillator (ICD) shocks to adverse clinical outcomes. Objective: To examine the association between inappropriate ICD shocks and mortality or heart transplantation in a large population cohort. Design, setting, patients: A cohort study which included all subjects who underwent ICD implantation between 1998 and 2008 and were followed up at our institution. Main outcome measures: Multivariable Cox regression analyses were conducted to investigate the effect of inappropriate shocks on the risk of death and heart transplantation. Appropriate and inappropriate ICD therapies were modelled as time-dependent covariates. Results: A total of 1698 patients were included. During a median follow-up of 30 months, there were 246 (14.5%) deaths and 42 (2.5%) heart transplants. The incidence of inappropriate shocks was 10% at 1 year and 14% at 2 years. In the adjusted model, inappropriate shocks were not associated with death or transplantation (HR=0.97, 95% CI 0.70 to 1.36, p value=0.873). In contrast, appropriate shocks were associated with adverse outcomes (HR=3.11, 95% CI 2.41 to 4.02, p value<0.001). The lack of association between inappropriate shocks and outcomes persisted for those with severely impaired  left ventricular function (ejection fraction <30%) and for those receiving multiple inappropriate treatments. Conclusions: In this study, we observed no association between inappropriate ICD shocks and increased mortality or heart transplantation, even among those with severely impaired cardiac function. These findings question whether inappropriate ICD shocks lead to adverse outcomes.